Os efeitos da Educação em Neurociência da Dor e Pilates na cinesiofobia de idosos com dor lombar crônica inespecífica: estudo clínico controlado randomizado - Campos, Mariane Marques de (Universidade Federal de São Carlos, 2018)
Non-specific chronic low back pain (NSCLBP) is considered one of the main complaints reported by the older people, leading to disability and decreased functional performance. The literature describes Pain Neuroscience Education (PNE) as an effective tool to modify beliefs and attitudes towards chronic pain, reducing kinesiophobia, pain intensity and disability when associated with exercises therapies. In the older people, Pilates Method (PM) exercises have been associated with improved kinesiophobia, pain intensity, disability, flexibility and balance. However, the effect of PNE associated with an exercise protocol in the older people is not yet known. Thus, this dissertation aimed to verify the efficacy of PNE associated with PM, compared to the PM, in kinesiophobia, pain intensity, flexibility, physical performance, mobility, functional balance and muscular electrical activity of the trunk extensor muscles in the older people with NSCLBP. Therefore, three studies were carried out. Study 1: "Effects of Pain Neuroscience Education associated to Pilates on kinesiophobia for older people with nonspecific chronic low back pain: protocol for a randomized controlled clinical trial". Objective: To describe the protocol used in a blinded randomized clinical trial, designed to combine PNE with PM as interventions for the treatment of NSCLBP in the elderly. METHODS: Eighty older people were randomly assigned to 2 groups (Education and Pilates Group - GEP and Pilates Group - GP), 40 people per group. Initially the GEP participated in 3 individual PNE sessions and then, the two groups participated in 16 Mat Pilates classes. A blind investigator evaluated kinesiophobia, pain intensity, flexibility, mobility and functional balance, physical performance and the electrical activity of the trunk extensor muscles before and after the interventions. Study 2: "The Effects of Pain Neuroscience Education and Pilates on Kinesiophobia in the older people with Non-Specific Chronic Low Back Pain: Randomized Controlled Clinical Study." Objective: To verify the efficacy of PNE associated to PM, compared to PM only, in improving kinesiophobia, pain intensity, flexibility, physical performance, mobility and functional balance of older people with NSCLBP. Results: There was no significant difference between groups in the studied variables. Conclusion: PNE was not effective in adding positive effects to PM practice in older people patients with NSCLBP, but it was effective in helping older people patients to adhere to exercise treatment. Study 3: "The Influence of Pain Neuroscience Education and Pilates on the muscular electrical activity of the older people with non-specific chronic low back pain". Objective: to evaluate if the PNE intervention associated with the PM exercises can alter the electrical activity of the trunk extensor muscles in functional tasks in the older people with NSCLBP. Results: there was a statistical difference between the groups, with a decrease in the electrical activity of the GEP after the intervention in the task of reaching in the amplitude and peak of the right longissimus muscle and amplitude of the left iliocostalis muscle. Conclusion: The association of END to PM exercises decreased the electrical activity of the right longissimus and left iliocostalis muscles, with maintenance in the performance in the reach task.
The effects of Pain Neuroscience Education and Pilates on kinesiophobia in the older people with non-specific chronic low back pain: randomized controlled clinical study
Keywords: Dor lombar; Idoso; Educação em saúde; Técnicas de exercício e de movimento; Low back pain; Aged; Health education; Exercise movement techniques; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE